Interface crack kinking in composite materials - Koh, Ben Kian Wen (2015)
The mechanisms and criterion for interface crack kinking in composite materials was investigated in this study. The theory of linear elastic fracture mechanics, particularly stress intensity factors, and crack tip opening displacement were used to establish the theoretical understanding of interfacial crack behaviours. Finite element modelling was used to verify the theoretical derivations from various researches done in the past. The simulation was done in three main stages: crack kinking in homogeneous materials; sub-interfacial crack kinking in composite materials and; interfacial crack kinking in composite materials. The FEM results were conclusive of the theoretical derivations which predicted the direction of crack propagation in composites and homogeneous materials as well as the criterion that determined if an interface crack embedded in the interface between two constituent materials of a composite would propagate along the interface or kink out into the more compliant constituent materials.